Translation, Cross-Cultural Adaptation, and Validation of the Croatian Version of the Athlete Psychological Strain Questionnaire (APSQ) - Katarina Sore; Frane Franic; Luka Androja; Ivana Batarelo Kokic; Darko Marčinko; Stipe Drmic; Zdravko Valentin Markser; Tomislav Franic (MDPI AG, 2024)
The aim of this study is to translate, cross-culturally adapt, and validate the Croatian Athlete Psychological Strain Questionnaire (APSQ-Cro) as part of the Sport Mental Health Assessment Tool 1 (SMHAT-1) validation. We assessed the reliability and applicability of the APSQ-Cro among Croatian athletes. The international sports community is increasingly focused on mental health issues in athletes, highlighting the need for early detection tools like the Athlete Psychological Strain Questionnaire (APSQ) and SMHAT-1. We included 869 Croatian competing athletes across 54 sports who received a link to access the WEB-based questionnaire. The Croatian Olympic Board helped in distributing the questionnaires, aiming to reach as many and as diverse a group of registered competing athletes in Croatia as possible. Results showed a Cronbach's alpha of 0.75 for the entire questionnaire, indicating acceptable reliability. An exploratory strategy of factor analysis was used to determine the underlying structure of the APSQ-Cro. For this purpose, the Kaiser-Meyer-Olkin (KMO) test and Bartlett's test for sphericity were performed to ensure the suitability of the data. The KMO test ensured sampling adequacy, with a measure of 0.77 indicating suitability for factor analysis, while Bartlett's test confirmed significant correlations among variables (χ2 = 2779.155, df = 45, p < 0.001), validating the dataset's appropriateness for data reduction techniques. The factor analysis, together with the Cattell scree test and varimax rotation, resulted in a two-factor structure for the APSQ-Cro. Factor 1 included items related to internal psychological struggles, while Factor 2 included items related to external pressures from the athletic environment. These two factors explained 53% of the variability, with Cronbach's alphas of 0.75 and 0.88 for the respective factors. The APSQ-Cro is a valid and reliable tool for assessing distress in Croatian athletes. Croatian athletes' sporting experience will be improved with the broad adoption of the APSQ-Cro, which can help detect early signs of psychological distress and subsequently improve mental health outcomes.